NSAID therapy for PIK3CA-Altered colorectal, breast, and head and neck cancer. (January 2020) - Cai, Yi; Yousef, Andrew; Grandis, Jennifer R.; Johnson, Daniel E.
Abstract: Epidemiologic evidence indicates that regular use of nonsteroidal anti-inflammatory drugs (NSAIDs) provides a protective effect against the development of colorectal, breast, and head and neck cancers. Genomic characterization of these cancers has lent considerable insight into the subpopulations of cancer patients who are most likely to benefit from NSAID therapy. The PIK3CA gene encodes the catalytic subunit of phosphatidylinositol 3-kinase (PI3K) and is among the most frequently mutated genes in solid tumor malignancies. Cancer-associated mutations in PIK3CA promote signaling via the PI3K pathway and stimulate tumor cell growth. In addition, activation of the PI3K pathway leads to induction of cyclooxygenase-2 (COX-2) enzyme and production of immunosuppressive prostaglandin E2 (PGE2 ). Notably, in both colorectal cancer and head and neck cancer the subpopulation of patients that benefit from NSAID use is restricted to those whose tumors exhibit PIK3CA genomic alterations. Preclinical studies, particularly in models of head and neck cancer, support the hypothesis that the chemopreventive impact of NSAIDs may be due, in part, to inhibition of COX-2 and reduction of PGE2 levels in the tumor microenvironment.